Padrões de diversidade e distribuição de anuros nos brejos de altitude do Ceará, Brasil - Araújo, Kássio de Castro (2021)
The humid forest remnants found in mountain regions of Brazilian semiarid called “Brejos de altitude” have been studied for over two decades and are underscored by the high herpetofaunal diversity, including some endemism and restricted species. However, little is known about the factors and processes that regulate the diversity and distribution patterns in these mountains. Thus, the present study had as main objectives 1) to test these “Brejos de altitude” biogeographical relationships regarding anuran composition; 2) to investigate the influence of altitudinal gradient, local and landscape metrics on anuran diversity and distribution; 3) and how some of these environmental features influence the species corporal condition; 4) besides to understand how cryptical species might coexist at same environment using a trophic ecology and habitat-use approach. For that, we collected data of 1,195 species in three of these “Brejos de altitude”, we consulted data available on literature and in the Núcleo Regional de Ofiologia da Universidade Federal do Ceará, Fortaleza, Brazil. Overall, we observed the “Brejos de altitude” of Ceará state are biogeographical units distinct from the other “Brejos” of the northeastern region, and altitude has no direct influences on diversity and distribution patterns, being the resources availability and hydrological regime the main drivers of anuran diversity in these locals. In addition, the anuran body size is affected differently due to each species inherent characteristics. Regarding the niche segregation patterns, we observed that the distinct habitatuse by two Adelophryne species allows these cryptical species live at the same local, once they have high niche overlapping.